(untitled) (Journal of the Bangladesh Agricultural University, 2020)
Dairy farmers’ profit is relatively low compared to the end user milk purchase price of Bangladesh. A lengthy debate has been running to pinpoint the reasons for this phenomenon. However, one of the trigger reasons is the milk farm gate price. Milk farm gate prices vary depending on the selling options used to flow the milk from producer to consumer. It also affects the farmers’ share with the consumers spending. An attempt was made to analyze the farmers’ share in existing selling options and factors of choosing the selling options in Sirajganj district of Bangladesh. The mathematical analysis of farmers’ share to consumer price and binary logistic regression method was used to make comparisons among different selling options of milk in peak and lean seasons. Primary data were collected from 130 commercial dairy farmers from major milkshed areas (Sirajganj district). A purposive sampling technique and survey questionnaires were followed to collect data from the dairy farmers in the research area. The major findings of the study showed that the dairy farmers did not use local breed for producing milk for business purpose and MilkVita was the major player of absorbing a major share of produced milk, although the farmers’ share was the highest for the Option-III (selling at the farmyard) where milk directly goes to the ultimate consumer without adding much utility to the product. In the peak and lean season, the model showed the variable of ‘amount of milk sold per day’ had a positive influence on the choice of milk selling option of MilkVita. The study concluded that MilkVita, other milk processors (Akij, BRAC, PRAN) and ghosh (middlemen) were popular milk selling options in the area because of guaranteed milk selling and several support services provided to dairy farmers. Thus, the policymakers can plan a policy to benefit the dairy farmers by setting up a mechanism of smoothly selling of produced milk ensuring reasonable farm gate price. J Bangladesh Agril Univ 18(2): 463–470, 2020 https://doi.org/10.5455/JBAU.82409